Growth and yield performance of zero tillage wheat (Triticum aestivum L.) under varying rice residue load and nutrient management options - Reddy, Mallepu S Likhitha; Mitra, Biplab (Journal of Cereal Research, 2023)
Conservation Agriculture (CA) based rice-wheat system improve overall productivity and profitability with improved production efficiencies and better environmental quality. Under CA it is very crucial to retain the residues, but to what extent? - still it is unanswered. There is an opportunity to manage nutrients in a more precise way under varying rice residue retained- wheat cultivation in sub-Himalayan plains of West Bengal. Keeping these in backdrop, a field experiment was conducted during the rabi season of 2021-2022 and 2022-2023 at Conservation Agriculture Block, Instructional Farm, Uttar Banga Krishi Viswavidyalaya, West Bengal to assess the impact of varying rice residue retention and nutrient management options on the growth and yield performances of subsequent zero tillage wheat. The experiment was laid out in split plot design having four main plot treatments of various heights of rice residue (rice straw kept at various heights after harvesting i.e., R0 – at ground level i.e., 0 cm, R1 - 15 cm, R2 - 30 cm and R3 - 45 cm) and five nutrient management options as sub-plot treatments (N1 - Control, N2 - Recommended dose of fertilizer (RDF), N3 - Nutrient Expert® (NE), N4 - RDF + Bio and N5 - NE + Bio), each replicated thrice. The wheat variety used in the experiment was DBW 187. Results revealed that rice residue retention did not show any significant effect on overall growth parameters, yield attributes and yield of wheat crop. However, higher grain yield (4.48 and 4.16 t ha-1) was obtained under the treatment R2 in which the rice straw was retained at 30 cm height. Nutrient management options had a significant impact on all growth parameters, yield attributes and yield of wheat. Results highlighted that management of nutrients in a balanced way as guided by NE® and seed inoculation with bio-fertilizers (N5) significantly improved spike no. m-2 (277 and 268), filled grains spike-1 (43.40 and 46.73), spike length (11.13 and 11.70 cm), 1000-grain weight (40.70 and 40.67 g) vis-a-vis higher grain yield (5.27 and 4.64 t ha-1) as compared to other treatments. Lower values of growth, yield attributes were obtained under the treatments where no above ground residues were kept (R0) and without any application of fertilizers (N1). It can be concluded that retention of residues at 30 cm height (R2) and nutrient management as guided by NE® along with seed inoculation with Azotobacter and PSB could increase the productivity of zero tillage wheat cultivation under this zone.